Genome‐wide association study and inbreeding depression on body size traits in Qira black sheep (Ovis aries). (6th June 2021) - Tao, L.; Liu, Y. F.; Zhang, H.; Li, H. Z.; Zhao, F. P.; Wang, F. Y.; Zhang, R. S.; Di, R.; Chu, M. X.
Summary: Qira black sheep is a famous indigenous sheep breed in China. The objectives of this study are to identify candidate genes related to body size, and to estimate the level of inbreeding depression on body size based on runs of homozygosity in Qira black sheep. Here, 188 adult Qira black sheep were genotyped with a high density (630 K) SNP chip and genome‐wide association study for body weight and body size traits (including withers height, body slanting length, tail length, chest girth, chest width, and chest depth) were performed using an additive linear model. In consequence, 12 genome‐ and chromosome‐wide significant SNPs and, accordingly, six candidate genes involved in muscle differentiation, metabolism and cell processes were identified. Of them, ZNF704 (zinc finger protein 704) was identified for body weight; AK2 (adenylate kinase 2) and PARK2 (parkin RBR E3 ubiquitin protein ligase) for tail length; MOCOS (molybdenum cofactor sulfurase) and ELP2 (elongator acetyltransferase complex subunit 2) for chest width; and MFAP1 (microfibril associated protein 1) for chest girth. Additionally, inbreeding depressions on body size were observed in the current herd. These results will provide insightful understandings into the genetic mechanisms of adult body size, and into the conservation and utilization of Qira black sheep.